Respostas
respondido por:
16
8.n! = (n+2).(n+1).n! +(n+1).n! / n+1
8.n! = (n+1) [(n+2).n! + n! ] / n+1
8.n! = n!.(n+2)+n!
8 = n+1 + 1
n+2=8
n=6
8.n! = (n+1) [(n+2).n! + n! ] / n+1
8.n! = n!.(n+2)+n!
8 = n+1 + 1
n+2=8
n=6
respondido por:
40
(n+2)!=(n+2)(n+1)n!
(n+1)!=(n+1)n!
8n!=((n+2)(n+1)n!+(n+1)n!)/n+1
simplifica o n+1 e o n!
fica 8=n+2+1
n=5
(n+1)!=(n+1)n!
8n!=((n+2)(n+1)n!+(n+1)n!)/n+1
simplifica o n+1 e o n!
fica 8=n+2+1
n=5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás